PEMBELAJARAN AYAT JURNAL PENYESUAIAN PERUSAHAAN DAGANG BAGI SISWA SMA KRISTOFORUS 1 JAKARTA - Lukman, Hendro; Sari, Vinnetta Ratna (Jurnal Serina Abdimas, 2024)
Adjusting Journal Entries in the process of preparing financial reports is a crucial stage. Adjusting journal entries are needed because in the accounting period there is still the possibility of income or expenses that do not yet show the actual balance. This happens because the accounting recording process regulates the concepts of deferrals and accruals so that the ledger balance recorded based on daily transactions does not show what it should. The process of making Adjusting Journal Entries is carried out after the ledger records are closed at the end of the period, so that Community Service (PKM) activities are carried out after the process of posting them to the General Ledger and creating a Trial Balance. This topic and discussion includes creating an Adjustment journal, calculating the adjusted amount and then entering it on the worksheet. PKM on this topic was given to students at Kristoforus 1 Jakarta High School. From the evaluation results, students can follow the process of making Adjusting Journal Entries and entering them in the working paper for the process of making financial reports. This activity is very good, for students to get more real questions, for partners as a differentiation from other schools, for universities as proof of service to stakeholders and promotion, and for students who take part in this activity to understand the knowledge gained better. went to college and became an Independent Learning activity at the Independent Campus. ABSTRAKAyat Jurnal Penyesuaian dalam proses penyusunan laporan keuangan merupakan tahapan yang krusial. Ayat Jurnal Penyesuaian diperlukan karena dalam periode akuntansi masih terdapat kemungkinan adanya pendapatan atau beban yang belum menunjukkan saldo yang sebenarnya. Hal ini terjadi karena dalam prosen pencatatan akuntansi mengatur konsep deferral dan akrual sehingga saldo buku besar yang dicatatan berdasarkan transaksi sehari-hari menjadi belum menunjukkan yang seharusnya. Proses pembuatan Ayat Jurnal Penyesuaian dilakukan setelah catatan buku besar ditutup pada akhir periode, sehingga kegaiatan Pengabdian Kepada Masyarakat (PKM) dilaksanakan setelah proses poating ke Buku Besar dan membuat Neraca Saldo. Topik dan pembahasan ini meliputi pembuatan urnal Penyesuaian, menghitung jumlah yg disesuaikan dan kemudian memasukkannya pada kertas kerja. PKM dengan topik ini diberikan kepada siswa Sekolah Menengah Atas Sekolah SMA Kristoforus 1 Jakarta. Dari hasil evaluasi, siswa dapat mengikuti proses pembuatan Ayat Jurnal Penyesuaian dan memasukan dalam kertas kerja untuk proses pembuatan laporan keuangan. Kegiatan ini sangat baik, bagi siswa untuk mendapatkan soal yang lebih real, untuk mitra sebagai salah satu deferensiasi dari sekolah lain, bagi perguruan tinggi sebagai bukti pelayanan kepada pemangku kepentingan dan promosi, dan bagi mahsiswa yang ikut dalam kegiatan ini menjadi lebih paham ilmu yang diperoleh dikuliah dan menjadi aktivitas Merdeka Belajar Kampus Merdeka